Immunosuppressive therapy maintenance in a kidney transplant recipient with SARS‐CoV‐2 pneumonia: A case report. Issue 7 (8th May 2020) - Bussalino, Elisabetta; De Maria, Andrea; Russo, Rodolfo; Paoletti, Ernesto
Abstract : The role of systemic inflammation is proving crucial in determining unfavorable outcome in SARS‐CoV‐2–infected patients. Limited data are available regarding immunosuppression management in kidney transplant recipients (KTRs) with SARS‐CoV‐2 pneumonia. We report a case of a 32‐year‐old KTR who developed SARS‐CoV‐2 infection and fully recovered in 15 days while maintaining standard immunosuppressive therapy. Abstract : In a renal transplant patient suffering from SARS‐CoV‐2 pneumonia, maintaining immunosuppressive therapy was associated with recovery, thus suggesting this choice is likely a useful strategy aimed at mitigating the risk of cytokine storm and improving clinical outcome.